﻿Massive splenomegaly and pancytopenia reuealing sarcoidosis in a child - ﻿Viprey, M.; ﻿Donadieu, J.; ﻿Epaud, R.; Coulomb, A.; Ducou Le Pointe, H.; Clement, A.; Fauroux, B.; Corvol, H. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Clinical presentation of sarcoidosis in children is very variable and dependant upon age. Herein, we report the first association of massive splenomegaly and pancytopenia as the revealing mode of sarcoidosis in an 8-year-old girl who, despite bone marrow involvement, had a remarkable good outcome following steroid therapy.